Social and Economic Outcomes of Fisheries Certification: Characterizing Pathways of Change in Canned Fish Markets - Anderson, Christopher M.; Himes-Cornell, Amber; Pita, Cristina; Arton, Ashleigh; Favret, Margaux; Averill, Dan; Stohs, Stephen; Longo, Catherine Sarah (Frontiers in Marine Science, 2021)
The Marine Stewardship Council (MSC) eco-labeling program provides fisheries a pathway to demonstrate their sustainability by undergoing an environmental certification. Like other standard-setters, the MSC’s ‘theory of change’ presumes that markets use this information to select for sustainable products, providing an incentive for producers to improve their practices and become certified. However, the underlying mechanisms which actually work to link market behavior and participation in the program in different contexts have not been systematically identified. We draw on broad MSC field experience to identify processes that have supported the theory of change in individual fisheries. Then, we develop a broadly applicable rapid assessment protocol, relying on a semi-structured interviews of key informants, to gather systematic evidence for key dynamics within the theory of change: the effects of going through MSC certification on market processes, partnerships in the fishery, and governance. In a pilot test of the protocol, we identify important common and idiosyncratic processes in three canned product fisheries: U.S. west coast albacore tuna, Brittany sardines, and Portuguese sardines. We find that the harvesters and buyers/processors in these fisheries sought certification primarily to expand or maintain their market share, and that certification was synergistic with stakeholder cooperation. The cases demonstrate how our rapid assessment interviews allow program participants to relate their experience in their own words yet facilitate systematic comparison to identify common mechanisms within the theory of change. We propose its wider application to systematically advance our understanding of social and economic processes that drive of eco-label interventions in different geographies and supply chains around the world.